ASSOCIATION BETWEEN MEDICATION USE AND BULLOUS PEMPHIGOID: A TEN-YEAR SYSTEMATIC REVIEW - Agnes Marpaung, Ronauli; Retnawati Sihombing, Fina (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Bullous pemphigoid is an autoimmune subepithelial disease. It was associated with autoantibodies targeting hemidesmosome protein BPAG1 and BPAG2. The incidence of bullous pemphigoid has increased 1.9-4.3 times in the past two decades, possibly due to increased life expectancy, medication use, and improved diagnostic methods. Trigger factors of BP included drugs, physical factors, radiotherapy, trauma, and thermal exposure. The aim: This study aims to determine association between medication use and bullous pemphigoid. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 1,662 articles, whereas the results of our search on ScienceDirect brought up 1,143 articles. The results of the search conducted by title screening yielded a total of 13 articles for PubMed and 32 articles for ScienceDirect. We compiled a total of 26 papers, 8 of which came from PubMed and 18 of which came from ScienceDirect. We excluded 2 review articles, 1 duplicate article, 3 non-full text articles, and 3 articles having insufficient outcomes. In the end, we included seventeen research that met the criteria. Conclusion: Our study suggests that dipeptidyl peptidase-4 inhibitors and aldosterone antagonists are associated with BP. Other medications, such as immunomodulatory agents, anticonvulsants, tyrosine kinase inhibitors, antibiotics, anticoagulants, diuretics, and mRNA COVID-19 vaccine, may be associated with BP. Regarding these results, clinicians should pay close attention to prescribing the medicine to their patients.